(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Katigraha is a Vataja Nanatmaja vyadhi and not explained as a separate disease, but rather as a symptom in another disease like as Ashmari, Arshas, Bhagandara etc. We have a brief summary of Katigraha along with symptoms, etiological causes, and treatment in Amavatadhikara Adhyaya of Bhavaprakasha, and in Vatavyadhi Adhikara of Gadanigraha. Along with specific symptoms like Katishoola and Katigraha caused either Shuddha or Sama vayu. In contemporary science, we can compare the Katigraha with low back pain (lumbago) suffering from Low back pain is an emerging problem in adolescents, with an incidence that is the highest in the third decade of life worldwide. Katibasti is the process in which, retaining of warm medicated oil in a specially formed frame prepared from Masha dough in lumbo-sacral region. It performs the combined action of Snehana and Swedana. Katibasti is a type of Snigdha Sweda, as warm oil is used which produce both the Snehana and Swedana effect, attempt has been made with Vishatinduka Taila for Katibasti purpose. In present study using Vishatinduka Taila Katibasti is done for 7 days for 30 minutes daily.